Tire road wear particles, microplastics and metals in sediment of stormwater detention basins: co-occurrence and ecological risk assessment - Zoé Iannuzzi; M. Carmen Casado-Martinez; Tiago De Oliveira; David Lebouil; Benoît J.D. Ferrari; Johnny Gasperi; Brice Mourier (Environment International)
Tire road wear particles (TRWP) and microplastics (MP) are increasingly present in the environment due to anthropogenic sources like industrial activities and road traffic. Their load is high in urban sediments and more specifically in stormwater management infrastructure such as detention basins. Eleven detention basins featured by contrasting land uses (industrial, urban, agricultural, and heterogeneous) were sampled in a French metropolitan city to examine how land use influences the presence of TRWP, MP, and metals in these basins. Results show that the concentration of TRWP is higher than MP in all samples, with the highest levels in industrial areas reaching 20,191 mg.kg−1 and 3,266 mg.kg−1, respectively. A positive and significant correlation is observed between urban related metals (Cd, Cu, Pb, Zn), TRWP and MP. The enrichment factor and pollution load index are used to classify the contamination of the basins and showed that all the basins are contaminated. Concerning the risk associated, a risk quotient is calculated for the three pollutants. A predicted non-effect concentration for sediments (PNECsediment) is proposed for TRWP specifically developed in this study using available effect data from the literature, which is set at 1,000 mg·kg−1. Two methods (polymeric risk index, risk score) are tested to consider the complexity of MP in the risk assessment, they are discussed in this study. The two methods show different results, highlighting the importance of considering the characteristics of MP in risk assessment.